Mechanism Design and Kinematics Analysis of Adaptive Rehabilitation Apparatus for Human Knee Joint - Tongtong Zhong; Zhixin Shi; Yufeng Luo; Dongfu Xie; Lingling Mo (Jixie chuandong)
The knee adaptive rehabilitation apparatus is designed， which consists of a swinging guide linkand a crank slider mechanism.According to ergonomics，the size range of the shank in the adaptive rehabilitation apparatus is determined by analyzing the motion characteristics of human knee joint. In order to realize the adaptive adjustment of the rotation angle of human knee joint， the kinematics model of the mechanism is established based on the complex vector method. According to the kinematics equation，the relation between the knee joint extension angle and the height of the movable frame in the mechanism is obtained， thus the size of the mechanism is determined. Through the simulation analysis and comparison between the adaptive rehabilitation apparatus and the traditional rehabilitation apparatus （crank slider mechanism）， the results show that the motion characteristics of the tandem type rehabilitation apparatus and the traditional rehabilitation apparatus （crank slider mechanism） can meet the stretching angle of the knee rehabilitation apparatus， but the motion stability of tandem type knee joint apparatus is better.